Estimasi Pengaruh Vaksin DPT pada Kematian Anak: Analisis Multivariabel data Survailan Demografi dan Kesehatan di Kabupaten Purworejo - Siswanto Agus Wilopo (Berita Kedokteran Masyarakat (BKM), 2009)
Background: Recent  controversial  reports  suggest  that  recipients  of  one dose  of DTP  vaccines had  higher mortality  than  children who  had  received  no DTP  vaccine. We   reanalyzed data  on vaccination  and  child  survival collected  from demographic  and health  surveillance  to  challenge previous  findings.Objectives: To estimate specific and non-specific effects of DTP vaccination on child mortality age 1-24 months under  routine vaccination  program  in  Indonesia.Methods: A  longitudinal  surveillance  data  provided  information  on 5647  children  below  24 months  of age who received DTP and  other vaccinations. The main  outcome measure was all-cause mortality. Background  factors associated with mortality were  collected,  such as:  sex,  birth  order, dead  sibling, mother’s  education and  family size. We assessed DTP vaccinations  as an  independent  factor with other  variables  in Cox’s  regression models with  time  dependent  covariates.Results: There  is  no  sex  differential  of mortality  among  children  in  Purworejo  even  after  considering  other factors using Cox  regression  analysis. Mortality was  lower  in  the  group  vaccinated with DTP vaccine  compared with  those  not  vaccinated,  the  relative  risk  of mortality  (RR)  being  0.56 with  95%  confidence  interval  (CI)  is 0.453–0.690. After controlling  for  the  background  factors,  recipient of DPT vaccines  continued  to  have  a  lower mortality with RR=0.74  (95% CI:  0.586–0.925). BCG  and measles  vaccines have  stronger  non-specific  effects compared  to  effects  of DTP  vaccines.Conclusion:    Through  specific  effect  against  targeted  diseases  and  a  non-specific  benefit  against  others illnesses,  the study  showed  reduced mortality among  children who  received DTP  vaccine. There  is no  reason to  change current  vaccination policy  because DTP was not  associated with  any  harmful  effect  among  girls.Keywords: non-specific  effects, DTP  Vaccine,  child  survival, Cox’s Regression